2005
DOI: 10.1158/1055-9965.epi-04-0907
|View full text |Cite
|
Sign up to set email alerts
|

Total Cholesterol and Body Mass Index in Relation to 40-Year Cancer Mortality (The Corfu Cohort of the Seven Countries Study)

Abstract: Purpose: We evaluated risk factors of cancer mortality based on a 40-year follow-up of the Corfu cohort (Seven Countries Study). Material and Methods: The population studied in this analysis consisted of 529 rural men (49 F 6 years old) enrolled in 1961. Since then, periodic visits every 5 years were made to define the causes of death of the participants. Cox proportional hazards models evaluated various risk factors in relation to cancer mortality. Results: The death rate at the end of the follow-up was 87.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Several studies have reported that cancer incidence [17], [18] and cancer mortality [19], [20] were lower in men with high baseline levels of TC. While this inverse association was seen in the majority of previous studies, others found cancer risk showed no relation at all [21], or a U-shaped association, with TC levels [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that cancer incidence [17], [18] and cancer mortality [19], [20] were lower in men with high baseline levels of TC. While this inverse association was seen in the majority of previous studies, others found cancer risk showed no relation at all [21], or a U-shaped association, with TC levels [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased serum cholesterol may also indicate a poor prognosis in liver cancer patients [71]. The paradox of the protective effect of total cholesterol levels on cancer risk, however, does not represent an etiological link (low cholesterol as a cause of cancer), but may reflect the advance of the clinical course of cancer (low cholesterol as an effect of cancer) [72]. In fact, total cholesterol synthesis was found to be lower in Yoshida AH130 ascites hepatoma tumour-bearing mice compared to controls [73].…”
Section: Discussionmentioning
confidence: 99%
“…For example, two reports from Scotland and the Netherlands could not identify any consistent significant trends between total cholesterol and deaths due to gastrointestinal, breast, lung, or ovary in their female cohorts [9,10]. Similarly, in a subcohort of Greek men from an international prospective study conducted from 1960 to 2000 (the Seven Countries study), an analysis of total serum cholesterol did not reveal any associations between higher values and overall cancer mortality [11]. In contrast, a Swedish health screening trial of 46,570 women, initiated in the 1960s, found that the relative risk of cancer mortality decreased with increases in serum cholesterol [12].…”
Section: Discussionmentioning
confidence: 99%